Studi kompetisi antara gulma teki dengan tanaman kacang tanah di lahan kering - Ngawit, I Ketut; Azhari, Anjar Pranggawan; Jihadi, Amrul (Universitas Muhammadiyah Mataram, 2025)
The research aims to determine the competition index and the maximum number of sedge populations that can be tolerated by peanut. In this regard, research has been carried out using additive, substitution and dynamic experimental models. The research results showed that the competition index of sedge when peanuts were 60 DAP was 0.0659 so that sedge were able to reduce peanut yields by 6.590%. Meanwhile, at 90 DAP the competition index is 0.0733, so that sedge have the potential to reduce peanut yields by 7.330%. The peanut yield loss calculated based on the weighted dominance variable is in accordance with the predictions of the sedge competition index, namely the yield loss of peanuts aged 60 DAP and 90 DAP is 66.00% and 72.60%. Meanwhile, based on the prediction of the sedge competition index, peanut yield losses were 65.90% and 73.30%. The growth of peanuts aged 60 DAP and 90 DAP began to be suppressed by the presence of 5.43 and 5.24 clumps per m2 of sedge, while for peanuts to suppress sedge growth, a population of 7.58 and 5.30 clumps per m2 was required. The presence of sedge that can be tolerated by peanuts aged 60 HST ≤ 5.43 clumps per m2 and aged 90 DAP ≤ 5.24 clumps per m2. The relative space occupation (RSO) of sedge when peanuts are 60 DAP is higher than the RSO of peanuts, whereas when peanuts are 90 DAP, the RSO of sedge is lower compared to the RSO of peanuts, namely the population density of peanuts and sedges 5-35 clumps per m2, the RSO value of peanuts is 57.00 – 94.00%, while the RSO value of nut weeds is 47.40 – 92.00%, with a comparative value of 9.60 – 2.00%